Implementation of the Occupational Safety and Health Management System in the Automotive Light Vehicle Engineering Workshop of Cokroaminoto Vocational School, Kotamobagu - Sanusi, Fadli M.; Rompas, Parabelem Tinno Dolf; Oroh, Rolly Robert (JR Education, 2023)
This research aims to determine the implementation of the Occupational Safety and Health (K3) management system in the Light Vehicle Engineering Automotive Workshop at Cokroaminoto Vocational School, Kotamonagu, which is based on the Occupational Safety and Health Management System. This research is a quantitative descriptive research. The research subjects were 3 respondents, namely 1 Head of Department, 1 Workshop Coordinator, and 1 Technician. Data was collected using a questionnaire and cross-checked with documentation and interviews. Testing the validity of the instrument is carried out through expert judgment. Data analysis is presented in the form of block graphs and presented briefly in tables in the form of percentages of achievement scores which are then categorized and described based on the sub-indicators. Based on the research results, the achievement of indicators in the implementation of the Occupational Health and Safety Management System in the Automotive Workshop for Light Vehicle Engineering at Cokroaminoto Vocational School, Kotamonagu, namely 73.57% achieved, falls into the sufficient category, because the implementation of K3 has been achieved sufficiently, so it is necessary to increase the implementation of K3 following the K3 management system. The obstacles that influence the implementation of SMK3 are the lack of awareness among students about the importance of K3, the absence of a special team that handles K3 at the Light Vehicle Engineering Automotive Workshop at SMK Cokroaminoto Kotamonagu and the lack of documentation at the Light Vehicle Engineering Automotive Workshop at SMK Cokroaminoto Kotamonagu. Efforts made to overcome obstacles are by providing direction and advice to students about the importance of K3 and students are advised to always use PPE when practicing. The need for a special team that handles K3 and documentation related to K3 must be improved so that the implementation of K3 in Automotive Workshops is run by regulations and legislation. When using tools, students must take part in maintaining and maintaining them so that the tools are not easily damaged and it is necessary to replace tools if one is damaged and add additional tools so that students do not have to take turns using the tools.